If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z+70=2(z+20)
We move all terms to the left:
z+70-(2(z+20))=0
We calculate terms in parentheses: -(2(z+20)), so:We get rid of parentheses
2(z+20)
We multiply parentheses
2z+40
Back to the equation:
-(2z+40)
z-2z-40+70=0
We add all the numbers together, and all the variables
-1z+30=0
We move all terms containing z to the left, all other terms to the right
-z=-30
z=-30/-1
z=+30
| t+942=1792 | | -2(x+5)+4=7x+14-3x | | 6b^2+3b-18=0 | | 4=-2x+9 | | 3(4x+4)-7x=-23-2x | | x-69=14 | | 3x*4x=147 | | 10+(2-x)=7 | | 3q+8=32 | | (3.5)2t+1=525.21875 | | 66=6k+6 | | 5-x/14=13/28 | | x+2x-5+71+123=360 | | 88=6m+58 | | 297=33c+99 | | 15/12x-25=0 | | 3x+-15=2x+10 | | x+2x-5+71+123=180 | | f(7)=2*7-3 | | -v/5=9.8 | | 3D+5=d-23 | | 33=8q-7 | | -7n+5=54 | | 4x-12=7(x+2)-3x | | 15.625=(2.5)t | | 5a=4a-6 | | 5/7d=35 | | 6x÷5=6 | | B-99=4b+6 | | (7x+6)+(6x-9)=180 | | q+10=53 | | 4x-6(6x-8)=-144 |